2008
DOI: 10.1159/000137642
|View full text |Cite
|
Sign up to set email alerts
|

Differential Impact of Lower Urinary Tract Symptoms on Generic and Disease-Specific Quality of Life in Men and Women

Abstract: Introduction: We investigated how generic and disease-specific measures differ in estimating the quality of life (QoL) impact of lower urinary tract symptoms (LUTS). Materials and Methods: A total of 172 men and 67 women ≧40 years old who attended the public lectures completed the questionnaire comprising the International Prostate Symptom Score, benign prostatic hyperplasia impact index and SF-36 Health Survey. The multiple regression analysis was performed to evaluate the QoL impact of LUTS. Results: Both st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
1
4
1
1
Order By: Relevance
“…In our study, we did not analyze the impact of each risk factor in different genders. Araki et al showed that the impact was gender-specific, 73 which could be the reason why we did not observe consistent results with previous studies for a few disease conditions. It will be interesting to test whether these risk factors for LUTS also play different roles in stroke patients of different genders.…”
Section: Discussioncontrasting
confidence: 88%
“…In our study, we did not analyze the impact of each risk factor in different genders. Araki et al showed that the impact was gender-specific, 73 which could be the reason why we did not observe consistent results with previous studies for a few disease conditions. It will be interesting to test whether these risk factors for LUTS also play different roles in stroke patients of different genders.…”
Section: Discussioncontrasting
confidence: 88%
“…The survey population is an important strength of our study. Younger individuals were not included because of previous data showing that LUTS are highly prevalent above the age of 40 [ 2 ] and numerous other epidemiological studies have focused on populations aged ≥40 years [ 6 , 7 , 9 , 12 , 47 ]. Additional strengths include the large number of participants and the use of well-established instruments to determine the presence and severity of LUTS and their effects on QoL and mental health.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Research on relative importance of symptoms indicated that storage symptoms exert greater bother on patients' QOL than voiding symptoms. [8][9][10] Contrarily, LUTS have low specificity to underlying disorders and are unreliable for the correct diagnosis, and storage and voiding symptoms do not necessarily reflect disorders of storage and voiding function, respectively. 11 There is weak or almost no correlation between LUTS and other clinical indicators such as prostate volume, urinary flow rate, residual urine volume, or the degree of infravesical (outflow) obstruction.…”
Section: Luts Comprise Important Elements In the Diagnosis And Assessmentioning
confidence: 99%